Eksplorasi Mengungkapkan Pesan di Balik Sebuah Lagu Sorai - Faizzatul Kiftiyah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This study aims to analyze the meaning of the lyrics of the song "Sorai" by Nadin Amizah and explore the factors that support its success in the Indonesian music industry. Using a qualitative descriptive approach, data were collected through an in-depth analysis of the lyrics and context of the song. The results showed the lyrics of the song "Sorai" contain deep emotional meanings about separation, love, and the process of maturity. Nadin's ability to string together simple yet meaningful poetic words is the main factor that touches the hearts of her listeners. This song is not only an aesthetic expression, but also a means of reflection on personal experiences that can build strong emotional connections with the audience.